Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Kepala Dinas terhadap Kinerja Pegawai di Dinas Perkebunan dan Peternakan Kabupaten Batang Hari - Niki Kosasih (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
This study aims to determine the respondents' responses about the Leadership Style and Work Discipline of the Head of the Service to the Performance of Employees at the Plantation and Livestock Service Office of Batang Hari Regency. This research is descriptive quantitative. The sampling technique used is the Arikunto formula, the sample in this study amounted to 44 respondents. Analysis of the data in this study using multiple linear regression techniques and using the SPSS 20 program. For the results of the study, the t-test where the Leadership Style variable from the research showed a value of (1.737 > 1.682), meaning that the Leadership Style variable had a significant effect on the Employee Performance variable and for the Work Discipline variable the results of the study showed a value of (1.704 > 1.682), meaning that the Discipline variable Work has a significant effect on employee performance. While for the F test, where F count > F table with a value of ( 4.005 > 3.23), it means that simultaneously the variables of Leadership Style and Work Discipline have a significant effect on employee performance at the Plantation and Livestock Service Office of Batang Hari Regency, and with a coefficient of determination (R2 ) obtained the Adjust R Square value of 0.123 or 12.3% and the remaining 87.7% is influenced by other variables not examined in this study